AKUNTING SUMBERDAYA ALAM DAN LINGKUNGAN KABUPATEN SOLOK - Rony M Bishry (Jurnal Teknologi Lingkungan, 2007)
The natural resources and environmental accounting is an important toolto account the stock and the sustainable flow of natural resources aswell as the depletion occured in the utilization of natural resources. Thenatural resources stock and flow accounting is important for supportingthe policy of natural resources utilization for development. The naturalresource depletion accounting is to record the depreciation of naturalresource capital. For Kabupaten solok it is recorded that in the year of2005, its natural resources has the total economic rent of Rp.765.530.561.000,-. With the natural resource depreciation ofRp.141.479.680.000,- and correcting its economic growth by 0,6 % of itsGRDP in 2005.